Possibilities of using online communication in destination management - Becková, Helena (Melandrium, 2019)
Communication is an inseparable part of activities of any business subject. Evidently, that applies to destination management as well. Advanced destination management can’t do without quality communication. It is necessary to pay due attention to communication so that it can be effective. That means to monitor also new trends and possibilities that modern life offers in the sphere of communication. More and more the emphasis is put on online communication, which has become a phenomenon of our time and in many cases replaces traditional ways of communication gradually. The paper deals with contemporary communication trends and focuses on the tourism sector, specifically on the problems of its management. It examines particular means of online communication and possibilities of their use in destination management. It also explains the situation in the Czech Republic by way of an analysis concerning online communication of particular destination management organizations working in the Czech Republic and by evaluation of its status quo. On the basis of observed results it then put suggestions how it would be possible to make this communication more effective.
Možnosti využití on-line komunikace v destinačním managementu
Keywords: destination management; tourism; communication; destinační management; cestovní ruch; komunikace